(untitled) (KIUT Publication, 2025)
This article provides a comprehensive analysis of the theoretical foundations, role, and social significance of small businesses and private entrepreneurship. The author examines the contribution of small businesses to national economic development, their role in ensuring employment, increasing household incomes, and shaping the entrepreneurial environment. Using statistical, analytical, and comparative methods, the study compares the experiences of Uzbekistan with other countries, identifies existing challenges, and explores ways to address them. The article concludes with specific recommendations and proposals for promoting the development of small businesses.